Poetas do Folha do Norte nas aulas de Língua Portuguesa - Bitencourt, Consuelo Penelu (2019)
This research, linked to the Professional Master's Degree in Literature - Profletras, proposes a didactic intervention for the teaching of the genre writer's biography and the construction of a virtual library - www.poetasdofolhadonorte.wordpress.com, with writers from Feira de Santana who published in the newspaper Folha do Norte until the 1950s. It begins with the understanding that the literature produced in the city did not reach the classroom. To organize the pedagogical actions of the intervention, a didactic sequence was structured. We anchor the theoretical studies in Jouve (2002) and Petit (2008) that approach reading, Kleiman (2005) and Rojo (2012) on literacy, in addition to Street (2014) dealing with social literacy. In the genres of speech approach, the dialogue occurs with Bakhtin (2003), Marcuschi (2002) and Rojo (2015). Also, are presented the reflections of Borges (1941) and Chartier (2002), in the approach of writing. To deal with the genre of writer's biography, we dialogued with Carino (1999). The multimodal language and the digital literacy are discussed starting from Xavier (2005), Rojo (2013, 2015), Barton (2015) and Coscarelli (2016). The research also brings approaches based on the laws that regulate education in Brazil (1996, 1998, 2017) in addition to the assumptions of education for sustainability (UN, 2015) and (UNESCO, 2017). The notion of language is based on the philosophical foundations of Bakhtin (2003). The teaching of language is mediated through the socio-interactionism of Vygotsky (2010). In order to deal with the concept of networked society and planetary citizenship, we have dialogues with Castells (1999), Morin (2000) and Levy (2003). The methodological approach is based on Damiani (2012) to be applied in a class of students of the 9th year - elementary school. For that, a didactic sequence was constructed to teach the writer’s biography – Dolz, Noverraz and Schneuwly (2004), adapted from Barreiros and Souza (2015), using a didactic model of gender. As results, the research contributes with subsidies for the formation of the young reader in new spaces of learning and with the social and digital literacy of the students.